Cerebral systems in the pathogenesis of endogenous psychoses - Aníbal Silveira (Arquivos de Neuro-Psiquiatria)
Mental processes imply a harmonious functioning of psychic systems, assembled into larger units, psychic spheres (Table I). Their neurophysiological representatives are brain systems of areas and pathways (Fig. 1-4). Under functional and/or organic disturbances these systems originate the leading mental symptoms (Table II) characterizing the diverse endogenous psychoses: hence, the latter's distinctive patterns. Accordingly, understanding and classification of psychoses should rest on the pathogenic dynamisms, not on clinical description. This is why Kleist's and Leonhard's conceptions of the endogenous psychoses surpass any other to exist. Kleist stands among the founders of psychiatry, by describing the "degeneration psychoses" and many single psychoses, as well as redefining, isolating and clarifying the progressive ones, later on renamed as schizophrenias (Table III). Such pathogenic criterion may also be useful to define mental conditions other than psychoses, as hysteria, neuroses and psychopathic inferiority (Tables IV and V). One should consider here, besides the psychic systems and spheres involved, the way they were caught and the corresponding developmental phase. In Kleist's "degeneration psychoses" - cyclic or episodic (Table VI) - the systems and spheres are disturbed by functional transient processes due to latent dispositions, while his and Leonhard's schizophrenias (Table VII) show a rather progressive, deteriorating course. The nature of the disorder is itself genetically determined, as is either its confinement to one sphere or its spreading out. The spread out pattern, while exceptional in schizophrenia, represents a rule for the "degeneration psychoses", in discussant's mind. Both groups may have symptoms alike by involvement of the same sphere (Table VIII), but proper diagnosis is reached by taking pathogenesis into consideration.